Selected aspects of forest protection in international law - Kosieradzka-Federczyk, Agata (Studia Ecologiae et Bioethicae, 2018)
The issues related to forest protection in international law are dispersed in several regulations regarding various aspects of environmental protection. The existing state shows that these acts primarily introduce instruments for protection of the main objective of the conventions. The forest protection is treated as an accessory aspect. This applies i.a. to the Convention on Biological Diversity and the United Nations Framework Convention on Climate Change. In this situation, although forest protection is an issue that is part of global problems, it does not find legal international protection that would guarantee sustainable use of forest complexes, and thus safe implementation of functions performed by the forest.